The loser - Bernhard, Thomas, 1931-1989; Anderson, Mark M.; Dawson, Jack (New York : Vintage International, 2006)
Een monoloog over succes, mislukking, genie en bekendheid.
Keywords: Gould, Glenn -- Fiction; Pianists -- Fiction; Canada -- Fiction; Biographical fiction; Musical fiction